Dominica : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Financing Assurances Review. (IMF Staff Country Reports; Country Report, 2004)
This paper examines the First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility for Dominica. The authorities were encouraged by the stronger-than-envisaged performance, but considered it premature to change the macroeconomic framework. The recent encouraging developments on the growth front enhanced the credibility of the macroeconomic framework and increased the chances of success. The authorities embraced the ambitious structural reform agenda as a necessary course of action to address the complex problems faced by Dominica.